Printed temperature sensor based on self-doped conducting polymers. (1st December 2022) - Beaumont, Catherine; Lapointe, Rosalie; Beaupré, Patrick; Trudeau, Charles; Le Bouch, Nolwenn; Leclerc, Mario
Abstract: The printing of an efficient thermistor temperature sensor by using self-doped conducting polymers has been achieved. The use of a water-soluble polymer as the active material allows printing and processing in green solvents. The sensor showed a good sensitivity to temperature variations, with a temperature coefficient of resistance of −1.3%. The sensor also exhibited a better stability and reversibility towards humidity compared to the state-of-the-art poly(3, 4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS).